A biomechanical review of the techniques used to estimate or measure resistive forces in swimming - Sacilotto, G. B.D.; Ball, N.; Mason, B. R. (Journal of Applied Biomechanics, 2014)
Resistive or drag forces encountered during free swimming greatly influence the swim performance of elite competitive swimmers. The benefits in understanding the factors which affect the drag encountered will enhance performance within the sport. However, the current techniques used to experimentally measure or estimate drag values are questioned for their consistency, therefore limiting investigations in these factors. This paper aims to further understand how the resistive forces in swimming are measured and calculated. All techniques outlined demonstrate both strengths and weaknesses in the overall assessment of free swimming. By reviewing all techniques in this area, the reader should be able to select which one is best depending on what researchers want to gain from the testing.